Intramedullary spinal cord tuberculoma in a patient with AIDS. - Melhem, E R; Wang, H (American Journal of Neuroradiology, 1992)
Intramedullary spinal cord tuberculoma in a young, homosexual man with AIDS was detected with the use of MR and confirmed pathologically. MR findings were similar to those seen in other intramedullary lesions, eg, astrocytoma, ependymoma, hemangioblastoma, metastasis, lymphoma, and opportunistic infections. Delineation of the lesion improved with administration of Gd-DTPA; enhancement of the lesion, however, does not always correlate with true tumor margins at pathologic examination.